High Profile Sports: Healthy Or Deathly (Financially)? - Halim, Jessica; Teofilus, Teofilus (Jurnal Locus Penelitian dan Pengabdian, 2026)
The rise of high profile sports (HPS), such as padel, tennis, golf, boxing, and horse riding, continues to increase globally in Indonesia, driven by lifestyle trends, social visibility, and health awareness. This study investigates the determinants of individuals’ intention to try HPS by examining the roles of social acceptance, fear of missing out (FOMO), and sport literacy. Primary data were obtained from an online survey involving 211 respondents who were familiar with or interested in high-profile sports. Four variables were measured using Likert scales and analyzed through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), followed by moderated regression analysis using PROCESS Model 3. The results indicate that social acceptance does not have a significant direct effect on intention to try HPS (p=0.7724). However, FOMO significantly moderates the relationship between social acceptance and intention to try (p=0.0364), indicating that social acceptance becomes more influential when individuals experience higher levels of FOMO. In contrast, the three-way interaction among social acceptance, FOMO, and sport literacy is not significant (p=0.5029), suggesting that sport literacy does not strengthen the moderating role of FOMO. These findings suggest that intention to try HPS is shaped primarily by psychological-social dynamics. Social acceptance alone is insufficient to drive intention unless accompanied by FOMO, while sport literacy does not function as a higher-order moderator in this relationship. This study contributes to a clearer understanding of how social influence operates conditionally in the adoption of lifestyle-oriented sports in the Indonesian context.